Will China’s carbon-trading policy foster coordinated innovation in green technologies? - Jun Wang; Simin Hao (Data Science and Management, 2024)
Accelerating green innovation is crucial for achieving high-quality development in China. Despite this importance, empirical evidence on the harmonization techniques in the context of carbon-trading policies has been remarkably thin. To address this gap, we employed the difference-in-difference (DID) and spatial difference-in-difference (S-DID) models using panel data from 2007 to 2017 for 30 Chinese provinces. Our findings reveal that the carbon-trading policy contributes significantly to the coordinated advancement of green technologies across Chinese provinces and exhibits a local siphoning effect. Specifically, the pilot areas of the policy have attracted talent from neighboring regions, which has fostered local cooperation and promoted coordinated innovation in green technologies within the region.